(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: A cross-sectional descriptive study was conducted at Lao Cai provincial General Hospital No.2 from April to June 2024 to investigate the clinical and subclinical characteristics of hepatitis B virus infection across different ethnic groups. Methods: Quantitative study, cross-sectional descriptive design. Results: A total of 206 patients were included in the study, with a predominance of male participants (62.1%) and the majority aged between 31-50 years (51.9%). The Kinh ethnic group accounted for the highest number of hepatitis B virus cases (146 individuals, 70.9%). The most common clinical symptoms observed were loss of appetite (89.3%), dark yellow urine (83.5%), and jaundice (66.5%). Elevated liver enzyme levels (AST, ALT, and GGT) were most pronounced among the H’Mông and Dao ethnic groups, indicating more severe liver damage. Conclusion: The notable differences in clinical manifestations and liver injury among ethnic groups highlight the need for prioritized routine screening and liver function monitoring, especially among high-risk populations such as the H’Mông and Dao communities.